Physicochemical Properties and Biological Activities of Quinoa Polysaccharides - Xucheng Zhu; Guiyan Yang; Yingbin Shen; Liqiong Niu; Yao Peng; Haiting Chen; Haimei Li; Xinquan Yang (Molecules, 2024)
Quinoa, known as the “golden grain” for its high nutritional value, has polysaccharides as one of its sources of important nutrients. However, the biological functions of quinoa polysaccharides remain understudied. In this study, two crude polysaccharide extracts of quinoa (Q-40 and Q-60) were obtained through sequential precipitation with 40% and 60% ethanol, with purities of 58.29% (HPLC) and 62.15% (HPLC) and a protein content of 8.27% and 9.60%, respectively. Monosaccharide analysis revealed that Q-40 contained glucose (Glc), galacturonic acid (GalA), and arabinose (Ara) in a molar ratio of 0.967:0.027:0.006. Q-60 was composed of xylose (xyl), arabinose (Ara), galactose, and galacturonic acid (GalA) with a molar ratio of 0.889:0.036:0.034:0.020. The average molecular weight of Q-40 ranged from 47,484 to 626,488 Da, while Q-60 showed a range of 10,025 to 47,990 Da. Rheological experiments showed that Q-40 exhibited higher viscosity, while Q-60 demonstrated more elastic properties. Remarkably, Q-60 showed potent antioxidant abilities, with scavenging rates of 98.49% for DPPH and 57.5% for ABTS. Antibacterial experiments using the microdilution method revealed that Q-40 inhibited the growth of methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli (E. coli), while Q-60 specifically inhibited MRSA. At lower concentrations, both polysaccharides inhibited MDA (MD Anderson Cancer Center) cell proliferation, but at higher concentrations, they promoted proliferation. Similar proliferation-promoting effects were observed in HepG2 cells. The research provides important information in the application of quinoa in the food and functional food industries.